2002
DOI: 10.1034/j.1398-9995.2002.1o3449.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with asthma in Albania

Abstract: This survey provides limited evidence linking asthma with aspects of western lifestyle. It supports the hypothesis that opportunities for infection during early childhood and the consumption of fruit and vegetables protect against asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…Many cross-sectional studies have reported that a high fruit intake is associated with a lower risk of asthma symptoms [3][4][5][6][7][8][9][10][11][12], and the need for intervention studies using fruit for asthma symptoms has been highlighted [21]. The present study is the first to look opportunistically at the effect on asthma symptoms of a population-based intervention aiming to increase fruit intake in young children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many cross-sectional studies have reported that a high fruit intake is associated with a lower risk of asthma symptoms [3][4][5][6][7][8][9][10][11][12], and the need for intervention studies using fruit for asthma symptoms has been highlighted [21]. The present study is the first to look opportunistically at the effect on asthma symptoms of a population-based intervention aiming to increase fruit intake in young children.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of previous cross-sectional studies suggesting that fruit consumption may be an important exposure influencing asthma symptoms in both children [3-5, 10, 11] and adults [6][7][8][9]21], the absence of an effect of increase in fruit intake on measures of asthma symptoms requires consideration. There are several potential explanations for this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigated the effects of fruit and vegetable consumption on respiratory health: two case-control studies [11••,24]; three cohort studies [13,14••,30]; and seven cross-sectional studies [19,21,28,[31][32][33][34]. The influence of fruit and vegetable consumption on several outcome measures was assessed.…”
Section: Fruit and Vegetablesmentioning
confidence: 99%
“…Epidemiological studies have shown that a high intake of fruits and vegetables reduces the risk of incidence of allergic diseases. [1][2][3] These studies indicate that the consumption of fresh fruits and vegetables helps to suppress wheezing, allergic rhinoconjunctivitis, and allergic eczema in adults and children. Fruits and vegetables are rich in such antioxidants as vitamin C, vitamin E, flavonoids, and carotenoids.…”
mentioning
confidence: 99%